2018
DOI: 10.1063/1.5012877
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium substitution: A simple and economic way to improve UV sensing in ZnO

Abstract: UV sensing in pure ZnO is due to oxygen adsorption/desorption process from ZnO surface.Vanadium doping improves UV sensitivity of ZnO. Enhancement in UV sensitivity in doped ZnO is attributed to trapping and de-trapping of electrons at V 4+ & V 5+ -related defect states.An extra electron in the V 4+ state is excited under UV illumination while in absence of the same a trapping happens at the V 5+ state. An insight to the mechanism is obtained by an analytic study of the response phenomenon. Introduction:Ultrav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
(19 reference statements)
0
8
0
1
Order By: Relevance
“…Thus, vanadium (V 4+ or V 5+ ) incorporation can form defect states in between the conduction and valence bands of ZnO [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, vanadium (V 4+ or V 5+ ) incorporation can form defect states in between the conduction and valence bands of ZnO [26].…”
Section: Resultsmentioning
confidence: 99%
“…According to Srivastava et al [26] the valence state of vanadium controls the oxygen content and lattice dimensions. It was reported that both V 4+ and V 5+ ions are more electropositive than Zn 2+ ions.…”
Section: Resultsmentioning
confidence: 99%
“…In vacuum (2.4 × 10 −3 Torr, i.e., 0.4 Pa), the recovery time increases to several tens of minutes [13]. Numerous studies of ZnO show an enhancement in UV sensing due to doping of the material with di erent elements, including indium [5,6], vanadium [14], magnesium [15], aluminum [12,16,17], gallium [17], tin [18], manganese [19], nickel [20], and others. Di erent mechanisms have been proposed to account for these e ects.…”
Section: Resultsmentioning
confidence: 99%
“…Di erent mechanisms have been proposed to account for these e ects. In particular, the enhancement in UV sensitivity in vanadium-substituted ZnO is attributed to trapping and detrapping of electrons at V 4+ -and V 5+ -related defect states [14]. e enhanced response of Mg-doped ZnO nanoparticles is associated with unpaired electrons added to the photocurrent [15].…”
Section: Resultsmentioning
confidence: 99%
“…Таким образом, эксперименты в вакууме подтверждают, что уменьшение сопротивления нитей связано с процессами десорбции-адсорбции кислорода с их поверхности. Полученные результаты согласуются с [19] чению за счет легирования различными элементами, такими как индий [13,14], ванадий [20], магний [21], алюминий [18,22,23], галлий [23], олово [24], марганец [25], никель [26]…”
Section: -4unclassified